Nuclear Ssr4 Is Required for the In Vitro and In Vivo Asexual Cycles and Global Gene Activity of Beauveria bassiana - Wei Shao (American Society for Microbiology, 2020)
ABSTRACT Ssr4 serves as a cosubunit of chromatin-remodeling SWI/SNF and RSC complexes in yeasts but remains functionally uncharacterized due to its essentiality for yeast viability. Here, we report pleiotropic effects of the deletion of the ssr4 ortholog nonessential for cell viability in Beauveria bassiana, an asexual insect mycopathogen. The deletion of ssr4 resulted in severe growth defects on different carbon/nitrogen sources, increased hyphal hydrophilicity, blocked hyphal differentiation, and 98% reduced conidiation capacity compared to a wild-type standard. The limited Δssr4 conidia featured an impaired coat with disordered or obscure hydrophobin rodlet bundles, decreased hydrophobicity, increased size, and lost insect pathogenicity via normal cuticle infection and 90% of virulence via intrahemocoel injection. The expression of genes required for hydrophobin biosynthesis and assembly of the rodlet layer was drastically repressed in more hydrophilic Δssr4 cells. Transcriptomic analysis revealed 2,517 genes differentially expressed in the Δssr4 mutant, including 1,505 downregulated genes and 1,012 upregulated genes. The proteins encoded by hundreds of repressed genes were involved in metabolism and/or transport of carbohydrates, amino acids, and lipids, inorganic ion transport and energy production or conversion, including dozens involved in DNA replication, transcription, translation, and posttranslational modifications. However, purified Ssr4 samples showed no DNA-binding activity, implying that the role of Ssr4 in genome-wide gene regulation could rely upon its acting as a cosubunit of the two complexes. These findings provide the first insight into an essential role of Ssr4 in the asexual cycle in vitro and in vivo of B. bassiana and highlights its importance for the filamentous fungal lifestyle. IMPORTANCE Ssr4 is known to serve as a cosubunit of chromatin-remodeling SWI/SNF and RSC complexes in yeasts but has not been functionally characterized in fungi. This study unveils for the first time the pleiotropic effects caused by deletion of ssr4 and its role in mediating global gene expression in a fungal insect pathogen. Our findings confirm an essential role of Ssr4 in hydrophobin biosynthesis and assembly required for growth, differentiation, and development of aerial hyphae for conidiation and conidial adhesion to insect surface and its essentiality for insect pathogenicity and virulence-related cellular events. Importantly, Ssr4 can regulate nearly one-fourth of all genes in the fungal genome in direct and indirect manners, including dozens involved in gene activity and hundreds involved in metabolism and/or transport of carbohydrates, amino acids, lipids, and/or inorganic ions. These findings highlight a significance of Ssr4 for filamentous fungal lifestyle.